Análise da modernização agrícola cearense no período de 1996 e 2006 - Madeira, Soraia Araújo (2012)
The term Agricultural Modernization has been widely discussed since the 1960 until today. Authors discuss about this theme having as basis the process of agricultural modernization entitled "Green Revolution", which basically consisted in the use of modern techniques, those techniques being adopted both in the U.S. and in Japan, and have become widespread all over the world. Nationally the theme much discussed and circulated in mid 1970 includes changes in technical basis, ie, it is modernized agricultural production that makes intensive use of equipment and techniques, such as machinery and modern inputs, which allows obtaining highest yield in production, so modernization of agriculture would be synonymous of mechanization and use of techniques in agriculture. The agricultural modernization in Ceará became intense in the 1970, with the construction of large public irrigated perimeters, that linked public irrigation settlement projects, increased food production beyond colonization and incentives to family agriculture. So the general objective of this work is to describe the level of modernization of agriculture between the 184 municipalities of the state of Ceará from 1996 to 2006. Specifically, we sought to determine the factors representing the process of agricultural modernization in the municipalities of Ceará in the analyzed period, produce a mapping of agricultural modernization in Ceará in the analyzed period and characterize the municipalities in Ceará according to level of agricultural modernization in 1996 and 2006. As regards the source of data on indicators of modernization for municipalities in Ceará, were collected from the Census of Agriculture of the state of Ceará, in the years 1996 and 2006, published by the Brazilian Institute of Geography and Statistics (IBGE). For both methods was used as: Factor analysis for extraction of the main factors representative of the modernization process in the period studied, besides construction of an aggregate index by analyzing clusters of municipalities could establish that they had a greater or lesser propensity for modernization agricultural state of Ceará. The results show how the characterization of the municipalities in Ceará building on the level of agricultural modernization in the state in the years 1996 can perceive that the cluster 1 consists of 144 municipalities as factors that have contributed most to the formation of the same: F2 and F3. For composition of cluster 2, the factors that contributed most to the formation of the same were: F3 and F5, comprising 31 municipalities in Ceará. Already clusters 3 and 4 presented as representative of the same factors: F3, F4 and F2, F4 and F5 respectively. So, it is concluded from data of Agricultural Census 1995 - 1996 that predominates in the state of Ceará an agriculture rudimentary low technological level for most of the municipalities Featured. When analyzing the 4 clusters formed for the year 2006, we found that the first cluster formed by 99 municipalities with lower IMA, have as major contributors: F1 and F4. For composition of the cluster are two factors: F1, F2 and F3 and formation of clusters 3 and 4, totaling 4 municipalities, the factors most representative of the process are F1 respectively. It is concluded through the 2006 Agricultural Census that most of the cities studied have a propensity for modernization far below that desired.